2021
DOI: 10.1177/0309133321988850
|View full text |Cite
|
Sign up to set email alerts
|

Assessing urbanization’s contribution to warming in mainland China using satellite-estimated air temperature data

Abstract: The global surface air temperature (Ta) has increased significantly in the past several decades. However, it remains disputable how much effect rapid urbanization has had on warming trends in mainland China. In this study, a gridded Ta dataset was created using satellite data. Then, a series of satellite-based methods to evaluate the contribution of urbanization to warming were developed. Subsequently, the contribution of urbanization to warming during 2001–2018 was estimated. The national average Ta was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 64 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…As the negative impacts of natural disasters continue to escalate globally due to population growth, climate change, and rapid urbanization, there is an urgent need for multi‐hazard risk‐based decision‐making in urban planning and design (Cremen et al, 2023). Some studies have shown that urbanization has a significant impact on rising temperature and rainstorm in local scale of China, and may even contribute more than 50% to the local temperature increase (Chao et al, 2020; Kong, 2020; Kong et al, 2020; Sun et al, 2016, 2019; Yao et al, 2021). Beijing, the capital of China, is located in the northwest end of the North China Plain at the intersection of the Taihang Mountain and the Yanshan Mountain, with the North China Plain and the Bohai Sea in the southeast.…”
Section: Introductionmentioning
confidence: 99%
“…As the negative impacts of natural disasters continue to escalate globally due to population growth, climate change, and rapid urbanization, there is an urgent need for multi‐hazard risk‐based decision‐making in urban planning and design (Cremen et al, 2023). Some studies have shown that urbanization has a significant impact on rising temperature and rainstorm in local scale of China, and may even contribute more than 50% to the local temperature increase (Chao et al, 2020; Kong, 2020; Kong et al, 2020; Sun et al, 2016, 2019; Yao et al, 2021). Beijing, the capital of China, is located in the northwest end of the North China Plain at the intersection of the Taihang Mountain and the Yanshan Mountain, with the North China Plain and the Bohai Sea in the southeast.…”
Section: Introductionmentioning
confidence: 99%